Unveiling the eco-storytelling: multimodal layers of meaning in Greenpeace’s environmental videos - Krysanova, Tetiana (Харківський національний університет ім. В.Н.Каразіна, 2024)
This paper addresses eco-storytelling as the process of meaning-making in Greenpeace’s environmental videos, with a focus on semiotic and cognitive aspects within a multimodal framework. By combining insights from multimodal discourse analysis and cognitive semiotics, this study explores how Greenpeace’s videos construct environmental issues through the interplay of various modes across different layers of meaning. This study presents a semiotic space within Greenpeace’s videos, highlighting the interplay of signs at the core, involved in a situation and embedded in the worldview. This model allows differentiation of three layers of meaning within the videos: embodied, referential, and ideological. Eco-storytelling involves the strategic use of multimodal elements—visual and auditory modes, including verbal, nonverbal, and cinematic means. These elements construct narratives at embodied, referential, and ideological layers, aiming not only to inform about environmental issues but also to inspire viewers to engage in environmental stewardship and advocacy. The study examines the role of multimodal means in constructing each semiotic layer and investigates the process of conceptual integration based on Brandt’s theory of Mental Space Network. In this framework, embodied, referential, and ideological meanings interact through mental spaces to create a comprehensive narrative that underscores the urgency of environmental action. This research contributes to understanding the complex role of multimodal resources in eco-storytelling and highlights how Greenpeace’s videos foster environmental awareness.
Keywords: відео; video; Грінпіс; Greenpeace; мультимодальність; multimodality; когнітивна семіотика; cognitive semiotics; смислотворення; meaning-making; сторітелінг; storytelling